A biomechanical analysis of volleyball block jumps - Huang, C. (1993)
The purpose of this study was to quantify and compare the biomechanical variables that characterized advanced and intermediate volleyball players when performing the quick and middle block jumps. The performance of 24 subjects were videotaped in the sagittal plane and digitized with the Peak Performance Motion Measurement System at 60 Hz. The vertical ground reaction forces during the block jumps were recorded by an AMTI force platform sampling at 600 Hz. A Two-Way repeated measures ANOVA was performed on the dependent variables between skill levels and methods of blocking. Significant differences were found between the two skill levels on the vertical velocity of the body CG at takeoff, maximum displacement of the body CG, maximum height of the finger tip from the ground, and hip angle at takeoff. In addition, significant differences were also found between the two block jumps on the vertical velocity of the body CG at takeoff, maximum displacement of the body CG, maximum height of the finger tip from the ground, propulsive phase time, the hip, knee, and ankle angle during the crouch, and maximum vertical ground reaction force. It was concluded that the vertical velocity of the body CG at takeoff was an important variable for increasing jumping height. The quick block showed a shorter propulsive phase time and a greater peak vertical ground reaction force. The middle block indicated the opposite. It was commended that the plyometric exercise combined with actual blocking drills should be used during training to improve the blocking ability.